Public, private and communitarian: New administrative categories for Brazilian schools and the dispute over the public fund in education - Adrião, Theresa; Portela de Oliveira, Romualdo; Mocarzel, Marcelo (Education Policy Analysis Archives, 2022)
The article sheds light on an important change in the Lei de Diretrizes e Bases da Educação Nacional brasileira (LDB), which occurred through Federal Law 13.868 / 2019, which disqualified community educational institutions from the category of private institutions, thus creating a new categorization between the public and the private. We sought, through documentary analysis, to point out the actors behind this change and the possible consequences, especially the induction of privatist policies regarding the division of the public fund.